2018
DOI: 10.34172/ajcmi.2018.02
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lactobacillus Species Isolated From Traditional Dairy Products Using RAPD-PCR

Abstract: BackgroundAccording to the World Health Organization (WHO) and the Food and Agriculture Organization (FAO), probiotics are viable microorganisms providing the human body with many benefits if consumed sufficiently (1). Probiotics are generally of human resources and known as nonpathogenic bacteria (2,3). The most common bacteria used as probiotics are driven from lactic acid bacteria family and can normally be found in dairy products such as yoghurt, cheese, etc. Traditional dairies are full of such organisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Therefore, it is of primary importance to use techniques capable of discriminating among strains. Typing methods might be used to trace individual strains (Abdollahniya et al 2018). Several studies have reported success using random amplified polymorphic DNA polymerase chain reaction (RAPD-PCR) for the differentiation of LAB isolates (Rossetti and Giraffa 2005;Parente et al 2016;Abdollahniya et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is of primary importance to use techniques capable of discriminating among strains. Typing methods might be used to trace individual strains (Abdollahniya et al 2018). Several studies have reported success using random amplified polymorphic DNA polymerase chain reaction (RAPD-PCR) for the differentiation of LAB isolates (Rossetti and Giraffa 2005;Parente et al 2016;Abdollahniya et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Typing methods might be used to trace individual strains (Abdollahniya et al 2018). Several studies have reported success using random amplified polymorphic DNA polymerase chain reaction (RAPD-PCR) for the differentiation of LAB isolates (Rossetti and Giraffa 2005;Parente et al 2016;Abdollahniya et al 2018). Repetitive extragenic palindromic PCR (REP-PCR) is another powerful tool used to identify several types of LAB, including Lactobacilli (Gevers et al 2001;Dolci and Cocolin 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that polymorphic information content (PIC) oscillated between 15.9 and 34.4% using a 1,254 primer. The results obtained from that study also showed that diversity within species (with 94% of all variance) was more significant than diversity between species (with 6% of all variance) (Delshad et al, 2018). Although reports suggested that data obtained from RAPD analysis could be highly ambiguous, as each isolate was nearly identical to L. johnsonii by 16S rRNA sequencing, RAPD analysis of these isolates showed much sequence variation when compared with reference strain L. johnsonii (Doi et al, 2013).…”
Section: Rapdmentioning
confidence: 75%
“…Geographical influence on lactic acid bacteria also observed in Kusdianawati et al (2020) work. According to Abdollahniya et al (2018), Lactobacillus isolates showed highest genetic similarity and grouping together that were collected from geographically less distant location and sources. In the present study, isolates from same cluster showed more genetic similarity.…”
Section: Discussionmentioning
confidence: 99%